One-Step Synthesis of Bifunctional Nickel Phosphide Nanowires as Electrocatalysts for Hydrogen and Oxygen Evolution Reactions - Xiang, Dong; Zhang, Biao; Zhang, Hongsheng; Shen, Liangping (Frontiers in Chemistry, 2021)
The Ni2P nanowires were simply synthesized via a rapid one-step hydrothermal approach, in which deionized water, red phosphorus, nickel acetate and hexadecyl trimethyl ammonium bromide were used as the solvent, phosphor and nickel sources and active agent, respectively. The as-synthesized Ni2P nanowire clusters composed of uniform nanowires with length of about 10 μm and diameter of about 40 nm. The Ni2P nanowires exhibit enhanced electrocatalytic activity for both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). This work provides a good guidance for rational design of nickel phosphides with unique nanostructures for highly efficient overall water splitting.